The Profit and Berkah (Blessing) from Palm SAP Production to Gain Optimal Mashlahah in Rokan Hulu-Riau Province - Rosyetti, Rosyetti; Ghafar Ismail, Abdul; Naula Oktaviani, Rona (Universitas Islam Negeri Raden Intan Lampung, 2021)
Palm sap is produced from male flower bunches that are cut off and tapped. Palm sap tapped by palm farmers is valuable since it generates profit and blessing for farmers. This study aims to determine and analyze the production of palm sap by sugar palm farmers in Rokan Hulu Regency, Riau Province, which has reached the Optimal Mashlahah. The execution of mashlahah in production activities is laba and blessing. Thus, palm sap producers will be capable of determining the combination of laba and berkah in realizing optimal mashlahah. The non-technical content of blessings is found in resources (inputs), results (outputs), and the production process. The data analysis method used was a quantitative method with descriptive data analysis. The model used was the